2007
DOI: 10.1016/j.regpep.2006.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Tissue kallikrein infusion prevents cardiomyocyte apoptosis, inflammation and ventricular remodeling after myocardial infarction

Abstract: We investigated the effect of tissue kallikrein infusion on cardiac protection at acute and sub-acute phases after myocardial infarction (MI). Immediately after MI, rats were infused with purified tissue kallikrein, with or without icatibant (a kinin B2 receptor antagonist). Intramyocardial injection of kallikrein reduced myocardial infarct size and inhibited cardiomyocyte apoptosis at 1 day after MI associated with increased nitric oxide levels, Akt and glycogen synthase kinase-3β phosphorylation and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
(31 reference statements)
6
34
0
Order By: Relevance
“…The antiapoptotic effect of the KKS was also demonstrated in vivo [24,[42][43][44]. In rats, immediate tissue kallikrein infusion after myocardial infarction reduced myocardial infarct size and inhibited cardiomyocyte apoptosis along with decreased p38 MAPK phosphorylation [44]. Moreover, BK infusion in Dahl salt-sensitive rats fed with high-salt diet and tissue kallikrein infusion in rats with gentamicininduced nephrotoxicity ameliorated tubular cell apoptosis [24,42], which was associated with the attenuation of increased p38 MAPK phosphorylation and of decreased Akt phosphorylation, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The antiapoptotic effect of the KKS was also demonstrated in vivo [24,[42][43][44]. In rats, immediate tissue kallikrein infusion after myocardial infarction reduced myocardial infarct size and inhibited cardiomyocyte apoptosis along with decreased p38 MAPK phosphorylation [44]. Moreover, BK infusion in Dahl salt-sensitive rats fed with high-salt diet and tissue kallikrein infusion in rats with gentamicininduced nephrotoxicity ameliorated tubular cell apoptosis [24,42], which was associated with the attenuation of increased p38 MAPK phosphorylation and of decreased Akt phosphorylation, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, stretch-induced apoptosis in cultured alveolar type II cells was inhibited by BK [33]. The antiapoptotic effect of the KKS was also demonstrated in vivo [24,[42][43][44]. In rats, immediate tissue kallikrein infusion after myocardial infarction reduced myocardial infarct size and inhibited cardiomyocyte apoptosis along with decreased p38 MAPK phosphorylation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Modification of MSCs with the TK gene could provide enhanced cardiac protection possibly by TK's ability to activate the kinin B2 receptor, either dependent or independent of kinin formation, thereby attenuating myocardial injury through Akt signaling and nitric oxide production. 15 Although the contribution of kinins to the protective effects of TK-MSCs was not investigated in the present study, Koch et al showed that transgenic rats overexpressing TK have increased basal kinin levels that may be responsible for the improvement in cardiac function and remodeling in these rats after MI. 35 Furthermore, while no difference in infarct size and cardiac function was observed between the TK-MSC and GFP-MSC MI groups 1 day after MI, the effects of TK-MSCs on inflammation and apoptosis may lead to improvement in these areas over a longer period of time.…”
Section: Tk-mscs Promote Neovascularization In the Myocardium At 2 Wementioning
confidence: 64%
“…13, 14 Moreover, TK suppressed cardiomyocyte apoptosis in vitro and in vivo by inhibiting oxidative stress and activating Akt-mediated signaling pathways. 15 TK also attenuated cardiac inflammation, hypertrophy and fibrosis, and increased nitric oxide formation in rats after MI. 15 We demonstrated that administration of TK-modified MSCs in the kidney protected against ischemia-induced renal injury by suppression of apoptosis and inflammation.…”
mentioning
confidence: 85%
See 1 more Smart Citation